SISTEM INFORMASI PENGAWASAN TAMAN KOTA PADA DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KABUPATEN SIDOARJO - Achmad Alfian Fajriansyah; Nuril Lutvi Azizah; Ade Eviyanti (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Utilization of Information Technology at the Sidoarjo Regency Environment and Hygiene Service has a positive impact on service progress. Computerized systems create a very important part of today's technological advances and ease of communication. For this reason, the author wants to develop a computer system that can facilitate the work of the Sidoarjo Regency Environment and Sanitation Service to meet the needs expected by the environmental service or the community for the Sidoarjo city's landscaping environment. The goal obtained from this urban park monitoring information system is that people do not need to come to the environmental service office to do reporting and complaints if there is a park in the Sidoarjo area that needs to be fixed. The technique used in this application is the waterfall method and uses the codeigniter framework. the result of user testing is 68% with the highest observation aspect, namely whether the city park monitoring information system makes it easier for people to mix about landscaping in the Sidoarjo area.